Mindf*ck : Cambridge Analytica and the plot to break America - Wylie, Christopher, ....- (New York : Random House, 2019)
"Mindf*ck goes deep inside Cambridge Analytica's "American operations," which were driven by Steve Bannon's vision to remake America and fueled by mysterious billionaire Robert Mercer's money, as it weaponized and wielded the massive store of data it had harvested on individuals--in excess of 87 million--to disunite the United States and set Americans against each other. Bannon had long sensed that deep within America's soul lurked an explosive tension. Cambridge Analytica had the data to prove it, and in 2016 Bannon had a presidential campaign to use as his proving ground."--Amazon.
Genesis -- Lessons in failure -- We fight terror in Prada -- Steve from America -- Cambridge Analytica -- Trojan horses -- The dark triad -- From Russia with likes -- Crimes against democracy -- The apprentice -- Coming out -- Revelations -- Epilogue: on regulation: a note to legislators.
Keywords: Data protection -- Law and legislation; Fake news -- Social aspects; Internet in political campaigns -- United States; Political campaigns : United States -- Corrupt practices; Presidents -- Election -- 2016 -- United States; Social media -- History -- 21st century -- United States